2005
DOI: 10.1590/s0100-67622005000200002
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do manejo da entrelinha da seringueira sobre as propriedades químicas do solo, o estado nutricional e o crescimento

Abstract: RESUMO -O trabalho teve por objetivo analisar a influência do manejo do solo da entrelinha da cultura da seringueira (Hevea brasiliensis) sobre as propriedades químicas do solo, o teor de nutrientes e o crescimento da seringueira. Para isso, implantou-se a seringueira (clones PB 235 e RRIM 701) em Latossolo VermelhoEscuro, em 1992, no Município de Jaboticabal, SP. Os tratamentos consistiram do manejo da entrelinha com: grade, roçadeira e cultura de cobertura utilizando uma leguminosa kudzu tropical (Pueraria p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
(4 reference statements)
0
3
1
1
Order By: Relevance
“…The organomineral fertilization provided the less acid soil and a decrease in the potential acidity value, which is in accordance with Carvalho, Moreira, Cruz, Fernandes and Oliveira (2014), who found the same benefits in olive trees fertilized with 50% of organomineral. However, these results are different from those found by Centurion, Centurion, Roque, Prado and Natale (2005), who observed a high pH under a soil management with tropical kudzu (Pueraria phaseoloide L.) associated with rubber trees compared to the management using harrow and brushcutter. Nascimento, Silva, Roberval and Silva (2005) observed a decrease in acidity using legumes such as pigeon pea.…”
Section: Soil Chemical Attributescontrasting
confidence: 99%
“…The organomineral fertilization provided the less acid soil and a decrease in the potential acidity value, which is in accordance with Carvalho, Moreira, Cruz, Fernandes and Oliveira (2014), who found the same benefits in olive trees fertilized with 50% of organomineral. However, these results are different from those found by Centurion, Centurion, Roque, Prado and Natale (2005), who observed a high pH under a soil management with tropical kudzu (Pueraria phaseoloide L.) associated with rubber trees compared to the management using harrow and brushcutter. Nascimento, Silva, Roberval and Silva (2005) observed a decrease in acidity using legumes such as pigeon pea.…”
Section: Soil Chemical Attributescontrasting
confidence: 99%
“…However, the knowledge on which management practices cause less alterations in the physical properties is still very little and it is key for a better plantation development and soil conservation. The conventional management used in the region is harrowing, with some recommendations for trimmer and green manuring (Centurion et al, 2005). However, the management techniques have great influence in soils attributes and species development.…”
Section: Introductionmentioning
confidence: 99%
“…Ribon et al (2003), when studying Oxisols and Ultisols in the area, have observed that the management with trimmer favours the increase in soils density and reduce the soil's macro porosity, eventually causing harm to tree development. On the other hand, Centurion et al (2005), when studying the influence of types of management in the soil's chemical properties and rubber tree nutritional state and development, observed that trimmer is important for the soil-plant system. Centurion et al (1995) performed a study on rubber tree development in soils from São Paulo's plateau (Oxisols and Ultisols) and have verified that those have not presented limitations in physical properties, effective depth, texture and internal drainage in this crop's development.…”
Section: Introductionmentioning
confidence: 99%
“…These uses have already embodied in the new research, the user of Hevea brasiliensis to double-fitness, or being directed to clones for production of rubber and wood, making the crop more attractive and profitable, and as a honey plant and for the extraction oil seeds, thus also being used for fuel production (biodiesel). [1][2][3][4][5][6][7][8] For proper drying, the moisture content of wood should be adjusted gradually to the equilibrium moisture content desired. This control is done through periodic adjustments in temperature and relative humidity inside the greenhouse, given by a drying program, whose productions requires an understanding of the species drying behavior.…”
Section: Introductionmentioning
confidence: 99%